1967
DOI: 10.1524/ract.1967.7.23.153
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption of 147Pm from Solution on to Metal Surfaces

Abstract: BesumeOn a trouve que l'absorption ä la surface des metaux de '"Pm en Solution aqueuse pure depend fortement de la composition et du traitement prealable de ces surfaces metalliques. Les resultats indiquent qu'en general une couche stable d'oxyde ou d'hydroxyde est necessaire pour que l'absorption puisse se produire. D'autre part le mecanisme de l'absorption exige dans certains cas la presence d'un film non absorbant de sulfure ou de fluorure afin de pouvoir distinguer differents composes superficiels sur un e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1974
1974

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…ELCHHOLZ et al [1] studied the adsorption of some radioisotopes on glass and polypropylene, and concluded that plastic Containers were not necessarily superior to glass in tracer work. Many investigators [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have also reported on the adsorption properties of various radioisotopes on the surfaces of plastics and glass.…”
Section: Introductionmentioning
confidence: 99%
“…ELCHHOLZ et al [1] studied the adsorption of some radioisotopes on glass and polypropylene, and concluded that plastic Containers were not necessarily superior to glass in tracer work. Many investigators [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have also reported on the adsorption properties of various radioisotopes on the surfaces of plastics and glass.…”
Section: Introductionmentioning
confidence: 99%